Developing Legacy: Health Planning in the Host City of Porto Alegre for the 2014 Football World Cup. Issue 6 (21st October 2015) - Witt, Regina Rigatto; Kotlhar, Mauro Kruter; Mesquita, Marilise Oliveira; Lima, Maria Alice Dias da Silva; Marin, Sandra Mara; Day, Carolina Baltar; Bandeira, Andrea Goncalves; Hutton, Alison
Abstract: Aim: To describe the process adopted to identify, classify, and evaluate legacy of health care planning in the host city of Porto Alegre for the Football World Cup 2014. Background: There is an emerging interest in the need to demonstrate a sustainable health legacy from mass gatherings investments. Leaving a public health legacy for future host cities and countries is now an important part of planning for these events. Process: The Ministry of Sports initiated and coordinated the development of projects in the host cities to identify actions, projects, and constructions to be developed to prepare for the World Cup. In Porto Alegre, a common structure was developed by the coordinating team to instruct legacy identification, classification, and evaluation. This structure was based on international documentary analysis (including official reports, policy documents, and web-based resources) and direct communication with recognized experts in the field. Findings and Interpretation: Sixteen total legacies were identified for health surveillance (5) and health services (11). They were classified according to the strategic area, organizations involved, dimension, typology, planned or unplanned, tangible or intangible, territorial coverage, and situation prior to the World Cup. Possible impacts were then assessed as positive, negative, and potentiating, and mitigating actions were indicated. Conclusions: The project allowed the identification, classification, and development of health legacy, including risk analysis, surveillance, mitigation measures, and provision of emergency medical care. Although the project intended the development of indicators to measure the identified legacies, evaluation was not possible at the time of publication due to time. RR Witt, MK Kotlhar, MO Mesquita, MADS Lima, SM Marin, CB Day, AG Bandeira, A Hutton .Developing legacy: health planning in the host city of Porto Alegre for the 2014 Football World Cup .Prehosp Disaster Med .2015 ;30 (6 ):613 –617 .